Collaborative Governance In Achieving Sustainable Development Goals: A Conceptual Framework - Samodra Wibawa; Darulfa Aziza Nur’aini (Universitas Terbuka, 2020)
Following the Millenium Development Goals (MDGs), the United Nations published their resolution of Sustainable Development Goals (SDGs) in October 2015. This has driven and inspired development plan of almost every nation. The government of Indonesian (i.e. Bappenas) should have formulated a roadmap and action plan in early 2018. Many local governments, despite the lack of guidance, claimed that they had adapted the SDGs goals into their local policies. This article aims to provide a conceptual framework of collaborative governance in order to achieve the goals of SGDs in Indonesia. There will be identification of indicators and prerequisites for collaborative governance practice. In other words: what factors can stimulate the practice of collaborative governance towards the achievement of SDGs goals quickly, democratic and inclusively?